2013
DOI: 10.3390/ijerph10030980
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status is Significantly Associated with Dietary Salt Intakes and Blood Pressure in Japanese Workers (J-HOPE Study)

Abstract: The association of socioeconomic status (SES) with nutrients intakes attracts public attention worldwide. In the current study, we examined the associations of SES with dietary salt intake and health outcomes in general Japanese workers (2,266) who participated in this Japanese occupational cohort. SES was assessed by a self-administered questionnaire. Dietary intakes were assessed with a validated, brief, self-administered diet history questionnaire (BDHQ). Multiple linear regression and stratified analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Finally, despite performing adjustments for potential confounding factors, the presence of residual confounding is possible. For example, the data were not adjusted for indicators of the socioeconomic status, such as the level of education and household income (20), due to the lack of available data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, despite performing adjustments for potential confounding factors, the presence of residual confounding is possible. For example, the data were not adjusted for indicators of the socioeconomic status, such as the level of education and household income (20), due to the lack of available data.…”
Section: Discussionmentioning
confidence: 99%
“…Fazel et al showed that low income and low level of education were associated with poor hypertension-related knowledge among adults in southern Iran [15]. Other studies also revealed the relationship between SES and hypertension-related behavior [16,17,18,19]. Smokers with lower education showed less willingness to quit and fewer quit attempts and reported a younger age in their smoking history [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HCMV infection might be a marker of low socioeconomic status, which is closely related to higher risk of intraparenchymal hemorrhage caused by high salt and low fat intake. [26][27][28] Further studies concerning the mechanisms of HCMV infection with stroke are encouraged.…”
Section: Resultsmentioning
confidence: 99%